Comparative strain and deflection hardening behaviour of polyethylene fibre reinforced ambient air and heat cured geopolymer composites - Shaikh, Faiz; Fairchild, A.; Zammar, R. (Elsevier BV, 2018)
This paper compares strain hardening and deflection hardening behaviour of polyethylene (PE) fibre reinforced two types of geopolymer composites. The first composite is heat cured fly ash based geopolymer composite while the other is ambient air cured fly ash and slag blended geopolymer composite. Comparison is also made with counterpart ordinary Portland cement (OPC) based composite. Effect of different volume fractions of PE fibre on compressive strength, strain hardening and deflection hardening behaviour of above three composites is evaluated and a critical volume fraction of PE fibre is identified. Results show that both heat and ambient cured geopolymer composites exhibited better strain hardening and deflection hardening behaviour than their counterpart OPC based composite containing same volume fraction of PE fibre. Results also show that the geopolymer composites and cement composite containing PE fibre volume fractions of 0.75–1.0% exhibit the highest ultimate tensile strain, deflection at peak load and maximum number of multiple cracks than other fibre contents. Compressive strength of OPC composite is higher than that of both geopolymer composites. Among geopolymer composites, the ambient cured geopolymer (AGP) composite exhibited much higher deflection capacity at peak load than heat cured geopolymer (HGP) under three-point load. Similar behaviour is also observed in uni-axial tension. Scanning electron microscopic analysis shows adherence of higher amount of cement matrix and geopolymer gel on PE fibre in cement and heat cured geopolymer composite that that on PF fibre in ambient cured geopolymer composite. This indicates the likely hood of higher frictional bond of PE fibre with matrix in cement and heat cured geopolymer than in ambient cured geopolymer.